Pengaruh Return on Asset, Earning per Share, Total Asset Turnover, dan Ukuran Perusahaan terhadap Harga Saham: Studi Empiris pada Perusahaan Subsektor Farmasi yang terdaftar di Bursa Efek Indonesia Periode 2019-2025 - Melyana Putri; Ivo Rolanda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the effect of Return on Assets (ROA), Earnings Per Share (EPS), Total Asset Turnover (TATO), and Firm Size on stock prices of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2025 period. This research employed a quantitative approach using secondary data obtained from annual financial statements and stock price data published by the companies and the Indonesia Stock Exchange. The sampling technique used was purposive sampling, resulting in a final sample of 8 companies out of 15 pharmaceutical sub-sector companies that met the predetermined criteria. The data were analyzed using multiple linear regression with the assistance of IBM Statistical Package for the Social Sciences (SPSS) version 26. Prior to hypothesis testing, classical assumption tests were conducted to ensure that the regression model satisfied the required statistical assumptions. The findings reveal that Earnings Per Share (EPS) has a positive and significant effect on stock prices, indicating that higher earnings per share increase investor confidence and contribute to higher stock prices. In contrast, Return on Assets (ROA), Total Asset Turnover (TATO), and Firm Size do not have a significant effect on stock prices. These results suggest that investors in the pharmaceutical sub-sector place greater emphasis on a company's ability to generate earnings per share than on asset utilization efficiency or firm size when making investment decisions.